The role of marketing strategies in penetrating Southeast and East Asian markets - Friedrich von Kirchbach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
Over the last two decades, Southeast and East Asian developing countries have evolved into an economic growth pole of increasingly global importance. The pronounced trade orientation of the eight major countries - i.e. the ASEAN countries, Hong Kong, the Republic of Korea and Taiwan - has rendered their combined import volume larger than that of the Middle East, Africa or Latin America. In 1984, 8.7 per cent of total OECD countries' exports (without intra-EEC trade) went to this region, up from 5.2 per cent in 1970. In relation to European standards, the imports of these eight countries are substantial. They were equivalent to 51.4 per cent of external EEC imports in 1984. Against this background, the declining role of European companies in this region deserves attention.
Keywords: 330; Internationales Marketing; Multinationales Unternehmen; Südostasien; Ostasien